ATTITUDES OF AUDITORS IN THE REPUBLIC OF SERBIA ABOUT USING OF VIRTUAL MEETINGS - Jakovljevic, Nemanja; Jakovljević, Jovanka (Economic Outlook, 2022)
The Covid19 has significantly changed the way we live and work. The way viruses are transmitted and people become infected has caused social distancing and avoidance of mutual contacts, which is largely reflected in the way audit meetings are held, which, unlike the previous reliance on physical presence in the office and direct communication between members of the audit team and others moved to a new environment that can be considered virtual. In most cases, meetings are held using internet applications, which means without physical presence. The subject of the research is to examine the attitudes of respondents engaged in audit work on the use of virtual meetings in the audit. The main conclusion is that respondents believe that the use of virtual meetings in auditing is useful, but at the same time, they are not ready to fully adapt to the continuous use of virtual meetings, because they believe that in some cases physical presence meetings are more useful than virtual meetings.